2016
DOI: 10.5194/angeo-34-1243-2016
|View full text |Cite
|
Sign up to set email alerts
|

The story of plumes: the development of a new conceptual framework for understanding magnetosphere and ionosphere coupling

Abstract: Abstract. The name "plume" has been given to a variety of plasma structures in the Earth's magnetosphere and ionosphere. Some plumes (such as the plasmasphere plume) represent elevated plasma density, while other plumes (such as the equatorial F region plume) represent low-density regions. Despite these differences these structures are either directly related or connected in the causal chain of plasma redistribution throughout the system. This short review defines how plumes appear in different measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 95 publications
(101 reference statements)
1
24
0
Order By: Relevance
“…This is supported by Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) observations that saw a factor of 2 increase in topside TEC despite a decrease in n m F 2 . This suggests that irregularities during this storm may extend higher in altitude than the h m F 2 , consistent with Coster et al [] and Yuan et al [] which found that half of SED TEC is found above 800 km, Moldwin et al [] which reviewed the body of literature connecting plasmaspheric and SED plumes, and Yizengaw [] which connected the plasmapause to the midlatitude trough.…”
Section: Irregularity Altitudesupporting
confidence: 85%
“…This is supported by Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) observations that saw a factor of 2 increase in topside TEC despite a decrease in n m F 2 . This suggests that irregularities during this storm may extend higher in altitude than the h m F 2 , consistent with Coster et al [] and Yuan et al [] which found that half of SED TEC is found above 800 km, Moldwin et al [] which reviewed the body of literature connecting plasmaspheric and SED plumes, and Yizengaw [] which connected the plasmapause to the midlatitude trough.…”
Section: Irregularity Altitudesupporting
confidence: 85%
“…They also found that the SED plume collocates with either upward or downward field‐aligned currents (FACs) but appears equatorward of the peak of the Region 1 FAC in the dusk convection cell. Moldwin et al (2016) reviewed the recent observation results and possible generation mechanisms of plasmaspheric plume, SED plume, and equatorial plasma plume. Heelis (2017) and Coster et al (2017) classified an SED phenomenon into the midlatitude broad SED with the large spatial feature and the SED plume that expands from a high‐latitude portion of the broad SED toward higher latitudes near local noon.…”
Section: Introductionmentioning
confidence: 99%
“…The SED plume has been linked to the plasmaspheric drainage plume (e.g., Foster et al, , , ; Foster & Coster, ; Walsh et al, ; Yizengaw et al, ) and therefore has an important implication on the magnetosphere‐ionosphere coupling (Moldwin et al, ). Though the SED plume is a well‐observed storm‐time ionospheric phenomenon (e.g., Coster et al, ), what physical process that is mainly responsible for producing the plume is still a topic of debate.…”
Section: Introductionmentioning
confidence: 99%